Determinants of a Variety of Deviant Behaviors: An Analysis of Family Satisfaction, Personality Traits, and Their Relationship to Deviant Behaviors Among Filipino Adolescents - Dullas, Angelo Reyes; Yncierto, Kristine Danielle; Labiano, Mariel A.; Marcelo, Jerome C. (Frontiers in Psychology, 2021)
In previous decades, numerous involvements of adolescents in deviant behavior have been increasing, and previous researchers examined different variables that may influence these phenomena. This study was designed to look for the possible predictors of deviant behavior, as well as its association with family satisfaction and personality traits. The study was conducted on 1500 participants ages 12–19 years old from selected schools in Nueva Ecija. The researchers used the Deviant Behavior Variety Scale (DBVS) by Sanches et al. (2016). It consists of 19 items (minor and severe) of a variety of deviant action such as thefts, drug and alcohol consumption, verbal and physical aggression, possession of weapons, vandalism, truancy, lies and defiance of authority, and selling drugs among adolescents (Sanches et al., 2016). Out of 1500 samples, 1227 met the criteria for the deviant behavior scale. Descriptive and Inferential statistics such as Mean, sd, frequency, percentage, Regression analysis, Pearson-correlation, and Mann Whitney U test were used to analyze this study. The research found that there are differences in levels of deviant behavior (Minor and Severe infractions) among sexes. Results showed that female participants have higher tendency to engage in minor infractions of deviant acts, while males had a higher rate of participation in severe infractions of deviant acts. Moreover, there is a negative/inverse association between family satisfaction and deviant behavior. This implies that respondents who participate more in deviant behaviors are found to be less satisfied with their family life, while respondents who participate less in deviant behavior are more satisfied in their family life. Lastly, the current study found that personality trait-agreeableness is found to be the best predictor of deviant behavior among adolescents.